PENGUKURAN KEPUASAN MASYARAKAT TERHADAP PELAYANAN PEMBUATAN AKTA KELAHIRAN DENGAN METODE ANALISIS FAKTOR - Nursabit Abrori (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to find out how the level of community satisfaction with birth certificate services. This research encourages curiosity about the manufacture and satisfaction of the community in carrying out the process of making birth certificates. The research method is an analytical method by analyzing factors. The results of this study indicate that there are still shortcomings in the ease of access and processes; discipline, speed and clear service standards; on time and non-discriminatory in service. Factors that influence community satisfaction in the factor of making birth certificates are factor 1 (F1) of 0.711 (71.1%) namely officers, accuracy of service, service of officers and politeness of officers, factor 2 (F2) of 0.862 (86.2%) namely the appearance of the officer, the speed of response and timely guarantee and factor 3 (F3) of 0.828 (82.8%) namely the convenience of the place and the guarantee of legality